2008
DOI: 10.1016/j.jecp.2008.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Children’s understanding of directed motion events in an imitation choice task

Abstract: We investigated children's understanding of directed motion events using an Imitation Choice paradigm. Thirty-four children (mean age 33 months) watched a model act out an event containing a manner of motion (hopping or sliding), a motion path (up or down a ramp), and a goal (in or on a bowl). On the child's apparatus, the locations of the goal objects were different from the model so that the child had to choose whether to imitate the path or the goal of the model's event. Children's choice of which component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 20 publications
2
16
2
Order By: Relevance
“…It has been argued that elicited imitation is not simply a one-to-one mimicking but rather an interpretation of an event which depends on children"s abilities to perceive, map, recode and reproduce demonstrated stimuli. Hence, elicited imitation taps children"s cognitive processing (Gleissner, Meltzoff, & Bekkering, 2000;Wagner, Yocom, & Greene-Havas, 2008), and children"s errors in replicating target acts provide a window onto how they process demonstrated information. A range of competencies are thought to be involved in imitation behaviour, e.g.…”
Section: Nonverbal Imitationmentioning
confidence: 99%
“…It has been argued that elicited imitation is not simply a one-to-one mimicking but rather an interpretation of an event which depends on children"s abilities to perceive, map, recode and reproduce demonstrated stimuli. Hence, elicited imitation taps children"s cognitive processing (Gleissner, Meltzoff, & Bekkering, 2000;Wagner, Yocom, & Greene-Havas, 2008), and children"s errors in replicating target acts provide a window onto how they process demonstrated information. A range of competencies are thought to be involved in imitation behaviour, e.g.…”
Section: Nonverbal Imitationmentioning
confidence: 99%
“…This criterion deemed a minimal standard to ensure that children possessed the necessary motor and representational skills and that their behavior during the imitation choice phase represented a meaningful choice between the components (Wagner et al, 2008). Most of the children (66%) imitated the two action components already in the first direct imitation trial, 12% of the children needed two trials, 8% needed three trials, and 14% needed four trials.…”
Section: Direct Imitation Phasementioning
confidence: 99%
“…As can be seen in Table 1, the patterns of behavior were not evenly distributed in the two groups and in the trials with different verbal cues. Second, we calculated preference scores, indicating the degree to which children's behavior matched the model's demonstration of the movement or goal component in the given trials (see Wagner et al, 2008). Each trial was scored as +1 if the child performed the observed movement at the expense of the goal component, as -1 if the child performed the observed goal at the expense of the movement component, and as 0 if the trial demonstrated either of the other choices.…”
Section: Imitation Choice Phasementioning
confidence: 99%
See 1 more Smart Citation
“…However, further research would be needed to clarify this issue. For HHI, it was found that people shift to imitating the movement trajectories when the saliency of the goals is low [50][51][52]. Indeed we found that many subjects reproduced the curvedness of the robot's pointing movements even though this was only necessary to prevent the robot from hitting its knee.…”
Section: Discussionmentioning
confidence: 67%